2015
DOI: 10.1038/srep13411
|View full text |Cite
|
Sign up to set email alerts
|

Parity and Cardiovascular Disease Mortality: a Dose-Response Meta-Analysis of Cohort Studies

Abstract: Parity has been shown to inversely associate with cardiovascular disease (CVD) mortality, but the evidence of epidemiological studies is still controversial. Therefore, we quantitatively assessed the relationship between parity and CVD mortality by summarizing the evidence from prospective studies. We searched MEDLINE (PubMed), EMBASE and ISI Web of Science databases for relevant prospective studies of parity and CVD mortality through the end of March 2015. Fixed- or random-effects models were used to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 35 publications
5
57
1
Order By: Relevance
“…Adjustment variables were chosen primarily based on findings from previous studies as potential confounding variables. 8,16 They were age (continuous), body mass index (BMI; quintiles), sleep duration (<5, 6, 7, 8, and ≥9 hours=day), walking habit (almost never, 0.5, 0.5-0.9, and ≥1 hours=day), exercise (almost never, 1-2, 3-4, and ≥5 hours= week), smoking status (never, past, and current smoker), alcohol intake (never, past, and current drinker), education (primary school, junior high school, high school, and college), occupation (fulltime job, part-time job, self-employed, housewife, no job, and other), marital status (married, widowed, divorced, and never married), perceived mental stress (low, moderate, and high), history of hypertension (yes and no) and history of diabetes (yes and no). Furthermore, the number of delivery was also adjusted in the analysis for association between maternal age at first delivery and CVD mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adjustment variables were chosen primarily based on findings from previous studies as potential confounding variables. 8,16 They were age (continuous), body mass index (BMI; quintiles), sleep duration (<5, 6, 7, 8, and ≥9 hours=day), walking habit (almost never, 0.5, 0.5-0.9, and ≥1 hours=day), exercise (almost never, 1-2, 3-4, and ≥5 hours= week), smoking status (never, past, and current smoker), alcohol intake (never, past, and current drinker), education (primary school, junior high school, high school, and college), occupation (fulltime job, part-time job, self-employed, housewife, no job, and other), marital status (married, widowed, divorced, and never married), perceived mental stress (low, moderate, and high), history of hypertension (yes and no) and history of diabetes (yes and no). Furthermore, the number of delivery was also adjusted in the analysis for association between maternal age at first delivery and CVD mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with previous findings of U-shaped association between the number of deliveries and risk of CVD Reproductive History and Mortality From Cardiovascular Disease mortality. [4][5][6][7][8] Important findings were reported by the censusbased Israel Longitudinal Mortality Study II, which enrolled 62,822 women and showed that both nulliparity and higher number of deliveries were associated with increased risk of CVD mortality. The multivariable HRs of CVD mortality in women aged 45-64 years were 2.43 (95% CI, 1.49-3.96) for nulliparous and 1.64 (95% CI, 1.02-2.65) for eight deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological data suggest that increasing parity is associated with higher risk of cardiovascular disease (CVD) and stroke and late-life vascular comorbidities, including carotid atherosclerosis (3,4). However, recent reports suggest that parity has a significant protective effect against CVD mortality (5). The effect of parity on outcome following ischemic stroke is yet unresolved.…”
mentioning
confidence: 99%